The Efffect of Profitability, Fundings, and Financing for Corporate Social Responsibility Disclosure in Islamic Banking - Risti Lia Sari (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2020)
The purpose of this study is to analyze the effect of profitability, fundings, and financing on the disclosure of Corporate Social Responsibility in Islamic Banks in Indonesia. The sample used was 11 Islamic banks in Indonesia which were listed on the Indonesia Stock Exchange and consistently published financial statements and corporate social responsibility reports for the period 2012-2018. The analysis of this study uses the multiple regression method (multiple regression). The results of the study explained that Profitability, Fundings and Financing together have a significant positive effect on CSR (Corporate Social Responsibility). Constraints that are still commonly found in the implementation of CSR are cost issues, competent human resources, distribution of activities and determination of targets, forms of activities, licensing and regulatory issues, lack of partnerships, socialization of activities, understanding of implementation and evaluation in the field, and many persons who carry out illegal levies on the ground.